PENGARUH CITRA MEREK, KUALITAS PRODUK, PERSEPSI HARGA, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PRODUK HANASUI PADA MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS 17 AGUSTUS 1945 - Indah Pujianti; Istiono (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2026)
This study aims to analyse the influence of brand image, product quality, price perception, and promotion on the decision to purchase Hanasui products among students of the Faculty of Economics and Business, 17 August 1945 University, Surabaya. This study uses a quantitative approach with a questionnaire distribution method. The population of this study are students of the Faculty of Economics and Business, Universitas 17 Agustus 1945 Surabaya who know or have used Hanasui products. The research sample of 77 respondents was determined using purposive sampling technique. Data collection was conducted through a questionnaire with a 1-5 Likert scale. The data analysis technique used was multiple linear regression analysis with the help of SPSS version 25 software. The results showed that, partially, brand image, product quality, price perception, and promotion had a positive and significant effect on the decision to purchase Hanasui products. In addition, simultaneous testing also showed that the four independent variables together had a significant effect on purchasing decisions. The coefficient of determination (R2) value of 0.830 indicates that 83.0% of the variation in purchasing decisions can be explained by brand image, product quality, price perception and promotion, while the rest is influenced by other variables outside the research model